The interconnection of teacher empowerment and motivating styles: A comparative analysis of novice and experienced EFL teachers - Masoomeh Estaji; Shamileh Hafezi (East European Journal of Psycholinguistics)
This study intended to disclose perceptions of novice and experienced EFL teachers regarding the linkage of teacher empowerment and their choice of motivating styles. To this end, a mixed-methods research approach was adopted. In the quantitative phase, 156 EFL teachers (Experienced = 97, Novice = 69) completed the online questionnaires on teacher empowerment and motivating style. In the qualitative phase, 10 teachers (5 novice and 5 experienced) were asked to participate in a semi-structured interview. Quantitative results showed that Autonomy-Supportive motivation style (AS) had a significantly positive correlation with Decision Making, Professional Growth, Status, Self-Efficacy, Impact, and Total Empowerment among novice teachers, and a significantly positive correlation with Professional Growth, Status, Autonomy, Impact, and Total Empowerment among experienced teachers. Moreover, the qualitative findings revealed that, from both novice and experienced EFL teachers’ perspectives, teacher empowerment was found to influence choice of teacher motivating styles. Further qualitative findings presented that from novice and experienced teachers’ vantage point, empowering strategies like attending conferences, reading books and articles, and taking part in professional development programs can contribute to teachers’ choice of motivating styles. These results have potential implications for various stakeholders in L2 education who can gain insights into how to foster teacher empowerment as a way to direct teachers toward choosing an autonomy-supportive teaching style.